FUNDAMENTALS OF COMPLIANCE CONTROL ORGANIZATION IN THE ACTIVITIES OF COMMERCIAL BANKS (International conference on multidisciplinary science, 2025)
Compliance control is a cornerstone of effective governance in commercial banks, ensuring adherence to legal, regulatory, and ethical standards. This article explores the fundamentals of organizing compliance control, emphasizing its importance in mitigating risks, maintaining trust, and fostering operational integrity. Key components of an effective compliance framework, including risk assessment, policy development, training, technology integration, and internal audits, are discussed in detail. The article also highlights challenges such as regulatory complexity, cost implications, and technological barriers, offering best practices like adopting a risk-based approach, leveraging advanced technologies, and fostering a culture of compliance. By implementing robust compliance control systems, banks can enhance their reputation, ensure sustainability, and navigate the complexities of a dynamic regulatory landscape.